Properties of 3D-printed fiber-reinforced Portland cement paste. (May 2017) - Hambach, Manuel; Volkmer, Dirk
Abstract: First insights into a 3D-printed composite of Portland cement paste and reinforcing short fibers (carbon, glass and basalt fibers, 3–6 mm) are presented, resulting in novel materials that exhibit high flexural (up to 30 MPa) and compressive strength (up to 80 MPa). Alignment of the fibers, caused by the 3D-printing process is observed, opening up the possibility to use the print path direction as a means to control fiber orientation within the printed structures. Apart from completely dense cementitious bodies, hierarchically structured bodies, displaying precisely adjusted macroporosity, are presented, the latter exhibiting a unique combination of strength and materials efficiency.